2001
DOI: 10.1021/jm0010668
|View full text |Cite
|
Sign up to set email alerts
|

Nonpeptide Cholecystokinin-2 Receptor Agonists

Abstract: In the course of structural explorations around a series of potent CCK2 receptor antagonists, it was noted that simple N-methylation of the indolic N-H in the parent molecule gave rise to behavior in vivo that was consistent with the compound acting as an agonist. Exploration in vitro confirmed this property, and it was shown that the agonist action could be blocked by the reference CCK2 receptor antagonist, L-365,260. Further examples of this type of modification were explored, and a common theme with regard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…This last stacking aromatic interaction maintains the CCK2R in the CCK2R°conformation by preventing rotation of helix VI, a motion that is required for CCK2R°to CCK2R* conversion (14). Methyl substitution in the partial agonist JB93,242 not only introduced a steric repulsion, as previously proposed (15), but also eliminated the hydrogen bonding capability of the indole nitrogen with Thr-2.61, causing displacement of the ligand in the CCK2R°binding pocket. Interestingly, JB93,242 finally adopted a location in the CCK2R°similar to that found in the active conformation (CCK2R*).…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…This last stacking aromatic interaction maintains the CCK2R in the CCK2R°conformation by preventing rotation of helix VI, a motion that is required for CCK2R°to CCK2R* conversion (14). Methyl substitution in the partial agonist JB93,242 not only introduced a steric repulsion, as previously proposed (15), but also eliminated the hydrogen bonding capability of the indole nitrogen with Thr-2.61, causing displacement of the ligand in the CCK2R°binding pocket. Interestingly, JB93,242 finally adopted a location in the CCK2R°similar to that found in the active conformation (CCK2R*).…”
Section: Discussionmentioning
confidence: 60%
“…In an attempt to examine whether the hydrogen attached to the indole nitrogen was crucial for ligand activity, this hydrogen was substituted by a methyl. Surprisingly, the resultant compound, JB93,242, behaved as a partial agonist (15).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…There is an increasing number of studies reporting that slight modifications in ligand structure may translate into loss or gain of agonist function (25)(26)(27)(28)(29)(30). At the wild-type CCK-2R, the addition of two methyl groups to the S enantiomer of compound 3 markedly enhances ligand function (compare 2S and 3S in Table 1 and Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Mutation of nonconserved amino acids from transmembrane helices led to the identification of a single amino acid in the canine sequence (Leu355, TM VI) that is responsible for this reversal of specificity (38). In general, studies with so-called nonpeptide antagonists of CCK2R revealed that although the amino acid sequence homology of CCK2R in the different species is near 90%, the efficacy of the nonpeptide molecules to stimulate phospholipase C varied from 0 to 60% of the CCK-induced maximal response according to the species and the compound tested (L365,260, L740,093, YM022, PD135158, PD136,450, PD134,308) (39, 47, 48, 227,232,255,256). Incorporation of nonconservative amino acids in the human CCK2R sequence enabled identification of amino acids in transmembrane helices that account for these variations (47, 48).…”
Section: A Localization Of Ligand Binding Sitesmentioning
confidence: 99%